Bimetallic CoMoO4 Nanosheets on Freestanding Nanofiber as Wearable Supercapacitors with Long-Term Stability. (3rd March 2023) - Khadka, Ashwin; Samuel, Edmund; Joshi, Bhavana; Kim, Yong Il; Aldalbahi, Ali; El-Newehy, Mohamed; Lee, Hae-Seok; Yoon, Sam S.
Abstract : Currently, lightweight wearable energy storage devices are in great demand owing to their use in wearable electronics and energy-efficient electric vehicles. Freestanding carbon nanofibers replace the need for metal substrates while providing a rapid electrical network owing to their excellent electrical properties. Bimetallic oxides with multivalent oxidation states facilitate the rapid transfer of electrolytic ions owing to efficient Faradaic reactions, thereby enhancing the overall energy storage capability. In this study, CoO x @CNF was derived from ZIF-67 (zeolitic-imidazolate framework) @PAN-2MI fibers that were stabilized in air at 280°C and then annealed in argon at 900°C. Subsequently, Co was seeded on the annealed CoO x @CNF and subjected to a hydrothermal process in sodium molybdate dihydrate solution to grow CoMoO4 nanosheets, eventually forming bimetallic CoMoO4 @CNF. The concentration of sodium molybdate solution was varied to determine the optimal growth conditions for CoMoO4 nanosheets. The energy density of the optimal bimetallic CoMoO4 @CNF sample was 166.5  μ Wh cm -2 at a power density of 200  μ W cm -2 ; this represented a nearly twofold increase compared to that of the single metallic CoO x @CNF. Powering humidity sensors using only one CoMoO4 @CNF supercapacitor was demonstrated. The optimal sample remained stable during long-term galvanostatic charge and discharge cycles (N cyc = 30, 000 ) and retained 100% of its specific capacitance.